Investigation of Isoprene Dynamics During the Day‐to‐Night Transition Period. Issue 20 (17th October 2020) - Wei, Dandan; Alwe, Hariprasad D.; Millet, Dylan B.; Kavassalis, Sarah C.; Lew, Michelle; Bottorff, Brandon; Stevens, Philip S.; Steiner, Allison L.
Abstract: At the University of Michigan Biological Station during the 2016 AMOS field campaign, isoprene concentrations typically peak in the early afternoon (around 15:00 local time, LT) under well‐mixed conditions. However, an end‐of‐day peak (around 21:00 LT) occurs on 23% of the campaign days, followed by a rapid removal (from 21:00–22:00 LT) at rate of 0.57 hr −1 during the day‐to‐night transition period. During the end‐of‐day peak, in‐canopy isoprene concentrations increase by 77% (from 3.5 to 6.2 ppbv) on average. Stratification and weak winds (<3.4 m s −1 at 46 m) significantly suppress turbulent exchanges between in‐ and above‐canopy, leading to accumulation of isoprene emitted at dusk. A critical standard deviation of the vertical velocity ( σ w ) of 0.14, 0.2, and 0.29 m s −1 is identified to detect the end‐of‐day peak for the height of 13, 21, and 34 m, respectively. In 85% of the end‐of‐day cases, the wind speed increases above 2.5 m s −1 after the peak along with a shift in wind direction, and turbulence is reestablished. Therefore, the wind speed of 2.5 m s −1 is considered as the threshold point where turbulence switches from being independent of wind speed to dependent on wind speed. The reinstated turbulence accounts for 80% of the subsequent isoprene removal with the remaining 20% explained by chemical reactions with hydroxyl radicals, ozone, and nitrate radicals. Observed isoprene fluxes do not support the argument that the end‐of‐day peak is reduced by vertical turbulent mixing, and we hypothesize that horizontal advection may play a role. Key Points: Low turbulent mixing during clear and calm nights leads to accumulation of isoprene within the canopy Turbulent mixing accounts for 80% of the observed nighttime isoprene loss rates Isoprene flux measurements did not capture the majority of the removal of the accumulated isoprene